Necrotizing fasciitis of the breast: case report - Cunha, Ana Paula da; Viana, João Vitor Matachon; Ruela, Letícia Viana; Victor, Amanda Martinelli; Xavier, Filipe Rocha; Visconti, Victor Esteves; Baliza, Matheus Casali Silva; Silva, Romão Precioso (Mastology, 2021)
Necrotizing fasciitis is a severe soft tissue infection characterized by rapidly progressive diffuse necrosis of fascia and adjacent tissues, most reported in the abdominal wall, perineum, and extremities. Cases of idiopathic necrotizing fasciitis of the breast are rare and unrelated to risk factors. This study was conducted with a 19-year-old woman reporting mastalgia and phlogistic signs in her right breast, which evolved with serosanguineous blisters and extensive necrosis of the fascia and periareolar wall, characterizing the necrotizing fasciitis. Therefore, the authors aim to show the relevance of early diagnosis associated with prompt treatment and procedure for a better intervention outcome.